Holocene monsoon and sea level-related changes of sedimentation in the northeastern Arabian Sea. (August 2019) - Burdanowitz, Nicole; Gaye, Birgit; Hilbig, Lea; Lahajnar, Niko; Lückge, Andreas; Rixen, Tim; Emeis, Kay-Christian
Abstract: The Indian Monsoon and the westerlies strongly influence the sedimentation in the northeastern Arabian Sea by impacting rainfall and erosion on land and on biogeochemical processes in the ocean. To disentangle the terrestrial and oceanic processes, we analysed mineralogical and bulk geochemical components of a Holocene sediment core offshore Pakistan. Endmember modelling of grain sizes and principal component analyses (PCA) of major and trace elements identify the origin of sediments and their dominant mode of transport. Sedimentation processes during the early Holocene (10.8–8.2 ka BP) were influenced by the post-glacial sea level rise and orbitally forced strengthening of the Indian summer monsoon (ISM) and westerlies. This led to a shift from rather terrestrial-dominated towards a marine-dominated sedimentation, whereas the fluvial source shifted from the Makran rivers to the Hab River near Karachi. During the mid-Holocene (8.2–4.2 ka BP) a combination of weakening ISM and southward displacement of the ITCZ enhanced the influence of the westerlies, together decreasing river discharges and enhancing aeolian input (probably from the Sistan Basin region). This trend continued during the last ca. 4 ka when the increasing aridification of the Hab River catchment further increased the aeolian inputs. Solar and lunar driven short-term variations as well as Bond events known from the North Atlantic Ocean superpose these trends. They lead to a pronounced increase of fluvial inputs between 8.6–8.4 ka BP and at ca. 3 ka BP as well as to dry events around 4.2 ka and 1.2–1 ka BP. Our study highlights the increasing influence of the westerlies on the sedimentation processes in the northeastern Arabian Sea towards the late Holocene.